การพัฒนาโมเดลเชิงสาเหตุของความเข้าใจในการอ่านที่มีแรงจูงใจในการอ่านและความสามารถทางภาษาเป็นตัวแปรส่งผ่านของนักเรียนระดับประถมศึกษา - พิธพร นิโกบ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purposes of this research were as follows 1) To study and compare the level of reading comprehension of elementary students of different area and school size. 2) To develop the causal model of reading comprehension with reading motivation and language ability as mediators. 3) To examine the goodness of fit of the model with empirical data 4) To study direct effect and indirect effect of effecting toward reading comprehension with reading motivation and language ability as mediators. The sample, randomly selected using three-stage sampling, consisted of 487 elementary students in school under the jurisdiction of the office of basic education committee at Bangkok Metropolitan Region. Variables consisted of 5 latent variables : reading comprehension, language ability, reading motivation, background knowledge and school’s environment. The three research instruments were 1) The questionnaire measuring reading motivation factor, background knowledge factor and school’s environment factors with reliabilities of ranging from .7532 to .9098 2) Reading comprehension scale with reliability of 0.70 3) Language ability scale with reliability of 0.73. The research data was analyzed by employing descriptive statistic, t-test independent, Pearson correlation and Lisrel model analysis. The research findings were as follows 1) Reading comprehension of elementary students were a medium level. Students of large school had higher reading comprehension than students of medium school (p < .01). Reading comprehension of student who lived in different area weren’t different (p < .05). 2) The developed causal model was fit to the empirical data all goodness of fit indices satisfying the required criteria. (χ² =51.29, df = 79, p = 0.993, GFI = 0.990, AGFI = 0.971, RMR = 0.036) 3) Reading motivation and language ability are mediator variables that toward reading comprehension. Background knowledge and school’s environment had a significant indirect effect toward reading comprehension with reading motivation and language ability as mediator variables (p < .05). Language ability, reading motivation and background knowledge had a significant direct effect toward reading comprehension (p < .05). Language ability had the most significantly total effect toward reading comprehension (p < .05).